Genetic diversity analyses reveal first insights into breed‐specific selection signatures within Swiss goat breeds. (20th July 2016) - Burren, A.; Neuditschko, M.; Signer‐Hasler, H.; Frischknecht, M.; Reber, I.; Menzi, F.; Drögemüller, C.; Flury, C.
Summary: We used genotype data from the caprine 50k Illumina BeadChip for the assessment of genetic diversity within and between 10 local Swiss goat breeds. Three different cluster methods allowed the goat samples to be assigned to the respective breed groups, whilst the samples of Nera Verzasca and Tessin Grey goats could not be differentiated from each other. The results of the different genetic diversity measures show that Appenzell, Toggenburg, Valais and Booted goats should be prioritized in future conservation activities. Furthermore, we examined runs of homozygosity (ROH) and compared genomic inbreeding coefficients based on ROH ( F ROH ) with pedigree‐based inbreeding coefficients ( F PED ). The linear relationship between F ROH and F PED was confirmed for goats by including samples from the three main breeds (Saanen, Chamois and Toggenburg goats). F ROH appears to be a suitable measure for describing levels of inbreeding in goat breeds with missing pedigree information. Finally, we derived selection signatures between the breeds. We report a total of 384 putative selection signals. The 25 most significant windows contained genes known for traits such as: coat color variation ( MITF, KIT, ASIP ), growth ( IGF2, IGF2R, HRAS, FGFR3 ) and milk composition ( PITX2 ). Several other putative genes involved in the formation of populations, which might have been selected for adaptation to the alpine environment, are highlighted. The results provide a contemporary background for the management of genetic diversity in local Swiss goat breeds.